1992
DOI: 10.1073/pnas.89.22.10812
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced phosphorylation of the murine interleukin 3 receptor signals its cleavage.

Abstract: The murine interleukin 3 receptor (mIL-3R) is a heterodimer consisting of a 70-kDa a subunit and one of two alternative 120-kDa (3 subunits termed (1Ln3 and (3l. (3i.3 (originally called Aic2A) is capable of binding mIL-3 by itself, whereas .8c (Aic2B) does not bind any ligand on its own but increases the affinity of mIL-3, murine granulocyte/macrophage-colony-stimulating factor, and mIL-5 for their respective a subunits. Interestingly, although the mIL-3R does not possess tyrosine kinase activity, its JBnL3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…An attractive hypothesis would be that Cis targets the Epo receptor for degradation. It has been previously reported that the degradation of the IL-3 receptor ␤ chain required its ligand-induced phosphorylation (45). This mechanism is consistent with the hypothesis that Cis, which binds to the tyrosine-phosphorylated Epo and IL-3 receptors, could be responsible for the degradation of these receptors and for the termination of the activation process.…”
Section: Discussionsupporting
confidence: 76%
“…An attractive hypothesis would be that Cis targets the Epo receptor for degradation. It has been previously reported that the degradation of the IL-3 receptor ␤ chain required its ligand-induced phosphorylation (45). This mechanism is consistent with the hypothesis that Cis, which binds to the tyrosine-phosphorylated Epo and IL-3 receptors, could be responsible for the degradation of these receptors and for the termination of the activation process.…”
Section: Discussionsupporting
confidence: 76%
“…Previously, Mui et al (1992) reported that tyrosine phosphorylation of the IL3 receptor ,3 chain is the signal for its proteolytic cleavage to a 70 kDa fragment. The target molecule containing phosphotyrosine residues may become a substrate of the proteolytic machinery by binding to CIS.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-c-Kit monoclonal antibody (MAb) was a generous gift from L. Ashman (University of Adelaide, Adelaide, Australia). Antibodies to the N-terminal 15 amino acids of the PIL-3 subunit of the murine IL-3 receptor (IL-3R) were produced by immunizing rabbits as described previously (30). Rabbit antisera to the human IL-3R Pc subunit and to the mouse Ep receptor (EpR) were generated by immunizing animals with glutathione S-transferase (GST) fusion proteins containing the entire intracellular domain of the human IL-3R c subunit (18) In a previous study we demonstrated that IL-3, SF, and Ep all induce the tyrosine phosphorylation of Shc and its association with Grb2 (8).…”
Section: Methodsmentioning
confidence: 99%